Psychiatric Comorbidity among Non-Injecting Opioid Users - Sidhu, Nittu; Garg, Parshotam Dass; Singh, Manjit (International Journal of Innovative Research in Medical Science, 2018)
Background - Psychiatric comorbidity is strongly associated with opioid use. The earlier studies have focused on injecting drug users and their associated psychiatric comorbidities, while little attention is made on the other group, non injecting drug users. The aim of the study is to focus on socio-demographic profile and psychiatric co-morbidities among the non injecting opioid users. Material and Methods - The present study was conducted in the Psychiatry Department, Government Medical College, Amritsar. A sample size of 150 patients was taken who fulfilled the criteria of opioid dependence using ICD 10 criteria. MINI (Mini International Neuropsychiatric Interview) was applied to study the psychiatric co-morbidity among the non injecting opioid users. Statistical Analysis - Data was analysed using SPSS software version 21.0. Results - The mean age of the subjects was 31.74 ± 8.64 years. The majority of subjects were male, married, employed. Majority of subjects had used the opioids for less than 5 years. Heroin was the most commonly used opioid followed by tramadol followed by synthetic opioids. Anxiety disorders were the most common psychiatric comorbidity followed by depression. Conclusions - There is high prevalence of psychiatric co-morbidity in the non injecting drug users which is often ignored which leads to poor treatment outcome. Hence there is more need for screening and assessment of psychiatric disorders in non-injecting opioid users.